Nemiralisib in Patients with an Acute Exacerbation of COPD: Placebo-Controlled, Dose-Ranging Study - Fahy WA (International Journal of COPD, 2021)
William A Fahy,1 Farshid Homayoun-Valiani,2 Anthony Cahn,3 Jon Robertson,4 Alison Templeton,4 Wilhelmine H Meeraus,5 Robert Wilson,3 Mike Lowings,6 Miriam Marotti,7 Sarah L West,2 Maggie Tabberer,8 Edith M Hessel9 1Discovery Medicine, GlaxoSmithKline R&D, GSK House, Brentford, UK; 2Global Clinical Operations, GlaxoSmithKline, GSK House, Brentford, UK; 3Discovery Medicine, GlaxoSmithKline, Stevenage, UK; 4Biostatistics, GlaxoSmithKline R&D, Stevenage, UK; 5Respiratory Epidemiology, Value Evidence and Outcomes, GlaxoSmithKline R&D, GSK House, Brentford, UK; 6Regulatory Affairs, GlaxoSmithKline, GSK House, Brentford, UK; 7Safety and Medical Governance, GlaxoSmithKline R&D, GSK House, Brentford, UK; 8Value Evidence and Outcomes, GlaxoSmithKline R&D, GSK House, Brentford, UK; 9Refractory Respiratory Inflammation Discovery Performance Unit, GlaxoSmithKline, Stevenage, UKCorrespondence: William A FahyDiscovery Medicine, GlaxoSmithKline R&D, GSK House, Brentford, United KingdomEmail william.a.fahy@gsk.comBackground: Management of acute exacerbations of chronic obstructive pulmonary disease (COPD) is sometimes inadequate leading to either prolonged duration and/or an increased risk of recurrent exacerbations in the period following the initial event.Objective: To evaluate the safety and efficacy of inhaled nemiralisib, a phosphoinositide 3-kinase δ inhibitor, in patients experiencing an acute exacerbation of COPD.Patients and Methods: In this double-blind, placebo-controlled study, COPD patients (40– 80 years, ≥ 10 pack-year smoking history, current moderate/severe acute exacerbation of COPD requiring standard-of-care treatment) were randomized to placebo or nemiralisib 12.5 μg, 50 μg, 100 μg, 250 μg, 500 μg, or 750 μg (ratio of 3:1:1:1:1:1:3; N=938) for 12 weeks with an exploratory 12-week follow-up period. The primary endpoint was change from baseline in post-bronchodilator FEV1 at week 12. Key secondary endpoints were rate of re-exacerbations, patient-reported outcomes (Exacerbations of Chronic Pulmonary Disease Tool, COPD Assessment Test, St George’s Respiratory Questionnaire-COPD), plasma pharmacokinetics (PK) and safety/tolerability.Results: There was no difference in change from baseline FEV1 at week 12 between the nemiralisib and placebo treatment groups (posterior adjusted median difference, nemiralisib 750 μg and placebo: − 0.004L (95% CrI: − 0.051L to 0.042L)). Overall, there were also no differences between nemiralisib and placebo in secondary endpoints, including re-exacerbations. Plasma PK increased in a dose proportional manner. The most common adverse event for nemiralisib was post-inhalation cough which appeared to be dose-related.Conclusion: The addition of nemiralisib to standard-of-care treatment for 12 weeks did not improve lung function or re-exacerbations in patients with, and following an acute exacerbation of COPD. However, this study demonstrated that large clinical trials recruiting acutely exacerbating patients can successfully be conducted.Keywords: acute exacerbation, COPD, dose-ranging, nemiralisib